2011
DOI: 10.2478/v10181-011-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor and cytokine interactions in myogenesis. Part II. Expression of IGF binding proteins and protein kinases essential for myogenesis in mouse C2C12 myogenic cells exposed to TNF-α and IFN-γ

Abstract: The aim of the study was to examine potential interactions among IGF-I and proinflammatory cytokines, TNF-α and IFN-γ, in the regulation of local IGF-I bioavailability and cellular proteins mediating myogenic signals. We investigated levels of IGFBP-4, -5, -6, protein kinase Czeta (PKCζ), p38 and extracellular signal-regulated kinase (ERK1/2) in differentiating mouse C2C12 myoblasts. IGF-I significantly stimulated expression of IGFBP-5. TNF-α and IFN-γ attenuated the expression of IGFBP-4 and -6 under basal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this study, we observed that threonine deficiency up-regulated IFN-γ mRNA levels in the intestines of juvenile grass carp. In mice, it was found that IFN-γ could enhance the PKCζ levels ( 86 ) , which could up-regulate IKKβ and IKKγ but ignore IKKα expression ( 87 ) . Hence, we hypothesised that threonine deficiency up-regulated the IFN-γ mRNA levels, partly resulting in increasing PKCζ levels, thus leading to the up-regulation of IKKβ and IKKγ (not IKKα ) in fish intestines.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that threonine deficiency up-regulated IFN-γ mRNA levels in the intestines of juvenile grass carp. In mice, it was found that IFN-γ could enhance the PKCζ levels ( 86 ) , which could up-regulate IKKβ and IKKγ but ignore IKKα expression ( 87 ) . Hence, we hypothesised that threonine deficiency up-regulated the IFN-γ mRNA levels, partly resulting in increasing PKCζ levels, thus leading to the up-regulation of IKKβ and IKKγ (not IKKα ) in fish intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that growth factors play a variety of roles during muscle regeneration (Gospodarowicz et al, 1976; Inselburg and Applebaum, 1978; Linkhart et al, 1981; Florini et al, 1986; Olson et al, 1986; Allen and Boxhorn, 1989; Jennische, 1989; Jin et al, 1990; Yablonka-Reuveni et al, 1990; Anderson et al, 1991; Grounds, 1991; Harrington et al, 1992; Doumit et al, 1993; McFarland et al, 1993; Barnard et al, 1994; Coleman et al, 1995; Johnson and Allen, 1995; Jones and Clemmons, 1995; Lefaucheur and Sebille, 1995; Zdanowicz et al, 1995; Chambers and McDermott, 1996; Engert et al, 1996; Florini et al, 1996; Papadakis et al, 1996; Quinn and Haugk, 1996; Floss et al, 1997; Kurek et al, 1997; Lamberts et al, 1997; Barton-Davis et al, 1998; Damon et al, 1998; Springer et al, 1998; Tatsumi et al, 1998; Keller et al, 1999; Gowdak et al, 2000; Sheehan et al, 2000; De Deyne et al, 2002; Musaro et al, 2004; Wieteska-Skrzeczynska et al, 2011a,b). Using a mouse model, Menetrey et al (2000) found that direct injections of insulin-like growth factor-1 (IGF-1), basic fibroblastic growth factor (bFGF), and, to a lesser extent, nerve growth factor (NGF), led to enhanced muscle healing in lacerated, contused, and strain-injured muscle at 2, 5, and 7 days after injury.…”
Section: Muscle Regenerationmentioning
confidence: 99%
“…For example, in intact animals IL-1α elevated circulating IGFBP-1, effectively reducing IGF bioavailability (Benbassat et al 1999) pointing to the systemic mechanisms of cytokine catabolic effects. Regarding in vitro models, several studies reported the inhibition of myogenic effect of IGF-I (O'Connor et al 2008, Wieteska--Skrzeczyńska et al 2011, whereas others provided evidence for the contrary, i.e. synergistic interactions of cytokines with IGF-I system in controlling myoblast number and differentiation (Al-Shanti et al 2008).…”
Section: Introductionmentioning
confidence: 99%